Developing a strategic perspective for construction industry of Botswana (Construction Economics and Building, 2013)
The paper discusses the outcome of a study conducted to formulate the strategic perspective of the construction industry in Botswana. The study was sanctioned by the two influential entities namely the Ministry of Infrastructure and BOCCIM Construction Sector. The two entities not only represent the demand and supply side of the construction industry but also represent key professions, trades and interests of the industry. A focus group approach was used based on workshops to formulate the strategic perspective. Workshop participants were drawn from various organisations that play a role in the delivery of construction projects. Individually they also represented the various professions, trades, occupations and interests relating to the construction processes in Botswana. Specific statements for industry’s vision, mission, values and goals were formulated through constructive discussions and debates to describe the future desired state of the construction industry. These are to serve as guiding tools for the industry’s reform process. The paper provides a step by step approach that integrates several scholastic frameworks for developing a strategic perspective for the industry.